Intersectional Experienced Stigma and Psychosocial Syndemic Conditions in a Sample of Black Men Who Have Sex with Men Engaged in Sex Work (BMSM-SW) from Six US Cities. Issue 7 (2nd September 2022) - Chandler, Cristian J.; Adams, Brian J.; Eaton, Lisa A.; Meunier, Étienne; Andrade, Elí; Bukowski, Leigh A.; Stall, Ronald D.; Friedman, M. Reuel
ABSTRACT: Black men who have sex with men (BMSM) in the United States experience a disproportionate burden of violence, substance use, physical and mental health conditions relative to other racial groups. BMSM who engage in sex work (BMSM-SW) experience a high burden of psychosocial conditions, sexually transmitted infections, including HIV, and intersectional stigma. This analysis characterizes remuneration and client typologies for BMSM-SW, documents intersectional stigma experienced by BMSM-SW relative to other BMSM, and explores the impact of experienced intersectional stigma on the relationship between sex work engagement and psychosocial syndemic conditions (violence, polydrug use, and depression symptoms). Results show that a majority of BMSM-SW in the sample had female clients and that sex workers were more likely than other BMSM to hire another sex worker. BMSM-SW were more likely than other BMSM to report stigma attributed to race; sexuality; HIV status; socioeconomic status; and "other" attributes, and were more likely to report experiencing stigma across all settings assessed (schools; healthcare; employment; housing; police/courts; and in public/community). Intersectional stigma mediated the relationship between sex work engagement and psychosocial syndemic conditions, accounting for 49% (95% CI: 47.6–50.0%) of the relationship. Interventions for BMSM-SW should include resilience-building components to counteract the effects of intersectional stigma.